Storytelling with data : a data visualization guide for business professionals - Knaflic, Cole Nussbaumer (Hoboken, New Jersey : Wiley, 2015)
Sometimes it is easy to generate charts and graphs look fine to you, but don't clearly communicate the information that they represent. Knaflic's own knack for clarity will help you sharpen your message when using data in your business presentations.
CASE STUDY 4: Strategies for avoiding the spaghetti graph -- CASE STUDY 5: Alternatives to pies -- In closing -- Chapter 10 final thoughts -- Where to go from here -- Building storytelling with data competency in your team or organization -- Recap: a quick look at all we've learned -- In closing -- Bibliography -- Index -- EULA
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 14, 2015).
Keywords: Information visualization; Computer graphics; Business communication; REFERENCE / Questions & Answers; Business communication; Computer graphics; Information visualization; Statistik; Visualisierung; Neue Medien; Electronic books